Male vs. female business owners: Are there differences in investment behavior? - Ines Pelger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper analyzes gender differences in the investment activity of German small and medium sized enterprises (SMEs). The empirical analysis is carried out on a sample of firms drawn from the KfW Mittelstandspanel, a representative survey of German SMEs for the period from 2003 to 2009. We find evidence that female-owned firms are less likely to invest and if they invest, then their average investment rate is lower. These differences cannot entirely be explained by firm or owner characteristics. Furthermore, women s investment is less sensitive to cash flow, which indicates that it is unlikely that their lower investment is driven by difficulties in acquiring external finance. An analysis of stated investment goals reveals that women have different preferences and attitudes towards investment. They indicate to a lesser extent aspiring and growth-orientated investment goals like sales increase, innovation/R&D or implementation of new products.
Keywords: J16; L26; G11; 330